Relationship between Water Quality and Distribution of Stonefly Larvae in Pristine Areas at Huai Nam Dung National Park, Thailand - Jaihao, Ratitorn; Phalaraksh, Chitchol (KKU Science Journal, 2013)
The aims of this study were to investigate how the distribution of stonefly larvae is related to the water quality of selected streams in Huai Nam Dung National Park, Thailand. Three streams were selected from pristine areas of the national park. Fifteen genera from four families were identified from this study. The highest total numbers of individual was found in genus Cryptoperla (47 individuals, 37.9%). The highest genera diversity was found from Mae Jok Stream (13 genera), and the highest total number of individuals specimens was also found from this stream (555 individuals). The Pearson’s Correlation value indicated the positive correlation between stonefly abundance and the elevation (r = 0.540, P < 0.01), and the negative correlation between stonefly abundance and many physico-chemical parameters especially water temperature (r = -0.481, P < 0.01) which revealed the highest negative correlation in this study. In order to consider the water quality using the Chemical Index, it was found that Nam Dung and Mae Ping Stream were found to be clean streams (Water temperature = 18.5, 19.1 °C, pH = 7.4, 6.9, Conductivity = 37.65, 26.99 µS/cm, BOD5= 0.6, 0.5 mg/l, NO3-N = 0.13, 0.08 mg/l, NH4-N = 0.91, 0.86 mg/l, O-PO4-P = 0.41, 0.28 mg/l), whereas the quality of Mae Jok Stream was in the fairly clean level (Water temperature = 20.2 °C, pH = 7.1, Conductivity = 44.78 µS/cm, BOD5 = 0.7 mg/l, NO3-N = 0.19 mg/l, NH4-N = 0.75 mg/l, O-PO4-P = 0.56 mg/l). The results of this study indicate that the high abundance of stonefly larva could be found in the streams, which were located in the pristine areas that undisturbed by human activity, and the environment was suitable for stonefly larva.